2021
DOI: 10.1001/jamanetworkopen.2021.12842
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Hospital Factors Associated With Differences in Mortality Rates Among Black and White US Medicare Beneficiaries Hospitalized With COVID-19 Infection

Abstract: IMPORTANCE Black patients hospitalized with COVID-19 may have worse outcomes than White patients because of excess individual risk or because Black patients are disproportionately cared for in hospitals with worse outcomes for all.OBJECTIVES To examine differences in COVID-19 hospital mortality rates between Black and White patients and to assess whether the mortality rates reflect differences in patient characteristics by race or by the hospitals to which Black and White patients are admitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 18 publications
6
75
0
Order By: Relevance
“…differences in individual characteristics (income, comorbid conditions) and hospital characteristics contribute to racial disparities in COVID-19 outcomes in the US [36]. The racial disparities in SOFA scores we found among patients with COVID might be due to the systemic overestimation of mortality among Black persons or underestimation of mortality among White persons.…”
Section: Plos Onementioning
confidence: 78%
“…differences in individual characteristics (income, comorbid conditions) and hospital characteristics contribute to racial disparities in COVID-19 outcomes in the US [36]. The racial disparities in SOFA scores we found among patients with COVID might be due to the systemic overestimation of mortality among Black persons or underestimation of mortality among White persons.…”
Section: Plos Onementioning
confidence: 78%
“…Recently, Asch et al showed that Black patients hospitalized with COVID-19 had 11% higher odds of death, as compared to White patients even following adjustment for sociodemographic characteristics between groups. Importantly, this group found that the higher mortality among Black patients can be explained in large part by having received treatment at hospitals that care for a disproportionate number of Black patients, suggesting that hospital segregation and inequitable distribution of resources are contributing to outcome disparities [ 15 ]. On the other hand, Yehia et al reported that hospital mortality was not higher in Black patients as compared to White patients diagnosed with COVID-19, citing mortality rates of 23.1% in hospitalized White patients and 19.2% in hospitalized Black patients within a cohort of 11,210 individuals [ 16 ], an encouraging finding dissimilar to previous literature reports but concurrent with that of this current study.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that black patients with COVID-19 usually had higher mortality rates that white patients, which was also noted among pediatric patients. However, the racial disparities are more like to be multifactorial while black race alone was not associated with the high mortality rates (109)(110)(111). Black patients had higher prevalence of chronic diseases, such as diabetes, hypertension, chronic renal diseases and so forth.…”
Section: Skeletal Complicationmentioning
confidence: 99%